2014
DOI: 10.1155/2014/213790
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism ofXRCC1,XRCC3, andXPDGenes and Risk of Chronic Myeloid Leukemia

Abstract: The genetic polymorphisms of X-ray repair cross complementing group 1 (XRCC1), X-ray repair cross complementing group 3 (XRCC3), and xeroderma pigmentosum complementation group D (XPD) repair genes may lead to genetic instability and leukemogenesis. The purpose of the study was to evaluate the association between XRCC1 Arg399Gln, Arg280His and Arg194Trp, XRCC3 Thr241Met, and XPD Lys751Gln polymorphisms and the risk of developing CML in Romanian patients. A total of 156 patients diagnosed with CML and 180 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 49 publications
2
35
0
1
Order By: Relevance
“…Among them, polymorphisms of X-ray repair cross complementing group 2 (XRCC2) have been studied extensively [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polymorphisms of X-ray repair cross complementing group 2 (XRCC2) have been studied extensively [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown different results (Xu et al, 2013;Bănescu et al, 2014;Xing et al, 2014;Bashir et al, 2015). Bănescu and colleagues reported that the XRCC3 Thr241Met polymorphism was not associated with the risk of chronic myeloid leukemia (Bănescu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bănescu and colleagues reported that the XRCC3 Thr241Met polymorphism was not associated with the risk of chronic myeloid leukemia (Bănescu et al, 2014). Xu and colleagues revealed that XRCC3 Thr241Met polymorphism was not associated with the development of lung cancer in a meta-analysis (Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Los polimorfismos gené-ticos de las enzimas implicadas en estos procesos de reparación van a determinar su capacidad funcional, pudiendo conducir a una menor capacidad de reparación del ADN, que puede ser la base de una tasa de mutación más alta, y como consecuencia última provocar un aumento de riesgo de desarrollo de procesos tumorales [33][34][35] . Los polimorfismos en ERCC1 y ERCC2 han sido asociados a un mayor riesgo para el desarrollo de cáncer de piel, cáncer de mama y cáncer colorectal [36][37][38][39][40] .…”
Section: Metabolismo Hidrocarburos Aromáticos Presentes En El Humo Deunclassified